Effects of granulocyte-macrophage colony-stimulating factor and cyclic AMP interaction on human neutrophil apoptosis - Cosimo Tortorella; Giuseppina Piazzolla; Felice Spaccavento; Salvatore Antonaci (Hindawi Limited, 1998)
The current study was undertaken to evaluate the effects of granulocyte-macrophage colony-stimulating factor (GM-CSF) and cyclic AMP (cAMP) signaling interaction on human neutrophil apoptosis, either occurring spontaneously or induced by Fas antigen activation. Results show that GM-CSF, dibutyryl cAMP (a cAMP analog) and forskolin (an adenylate cyclase activator) are all able to suppress spontaneous neutrophil cell death. Of note however, when GM-CSF is used in combination with cAMP-elevating agents, an additive effect on neutrophil survival is observed with dibutyryl cAMP only, whereas supplementation of cell cultures with GM-CSF and forskolin results in a progressive reduction of antiapoptotic effects exerted by the single compounds. Moreover, although dibutyryl cAMP and forskolin do not affect Fas-triggered apoptotic events, they are still able to modulate the GM-CSF capacity to prolong neutrophil survival following anti-Fas IgM cell challenge, with effects similar to those respectively exerted on spontaneous neutrophil apoptosis. The data indicate that GM-CSF m ay negatively modulate the cAMP-mediated antiapoptotic pathway in human neutrophils, likely via the inhibition of adenylate cyclase activity. This would prevent an abnormal neutrophil survival as a result of cAMP signaling stimulation, which provides a novel insight into the role of GM-CSF as a physiological regulator of myeloid cell turnover.